Low-Dose Metformin Reprograms the Tumor Immune Microenvironment in Human Esophageal Cancer: Results of a Phase II Clinical Trial - Wang, Shuhong; Lin, Yusheng; Xiong, Xiao; Wang, Lu; Guo, Yi; Chen, Yuping; Chen, Shaobin; Wang, Geng; Lin, Peng; Chen, Hongcai; Yeung, Sai-Ching Jim; Bremer, Edwin; et al. (Clinical cancer research, 2020)
The tumor immune microenvironment (TIME) has an important impact on response to cancer immunotherapy using immune checkpoint inhibitors. Specifically, an "infiltrated-excluded"/"cold" TIME is predictive of poor response. The antidiabetic agent metformin may influence anticancer immunity in esophageal squamous cell carcinoma (ESCC). We analyzed matched pre- and posttreatment ESCC specimens in a phase II clinical trial of low-dose metformin treatment (250 mg/day) to evaluate direct anti-ESCC activity and TIME reprogramming. Follow-up correlative studies using a carcinogen-induced ESCC mouse model were performed with short-term (1 week) or long-term (12 weeks) low-dose metformin (50 mg/kg/day) treatment. In the clinical trial, low-dose metformin did not affect proliferation or apoptosis in ESCC tumors as assayed by Ki67 and cleaved caspase-3 immunostaining. However, metformin reprogrammed the TIME toward "infiltrated-inflamed" and increased the numbers of infiltrated CD8 cytotoxic T lymphocyte and CD20 B lymphocyte. Further, an increase in tumor-suppressive (CD11c ) and a decrease in tumor-promoting (CD163 ) macrophages were observed. Metformin augmented macrophage-mediated phagocytosis of ESCC cells . In the ESCC mouse model, short-term metformin treatment reprogrammed the TIME in a similar fashion to humans, whereas long-term treatment further shifted the TIME toward an active state (e.g., reduction in CD4 FoxP3 regulatory T cells) and inhibited ESCC growth. In both humans and mice, metformin triggered AMPK activation and STAT3 inactivation, and altered the production of effector cytokines (i.e., TNFα, IFNγ, and IL10) in the immune cells. Low-dose metformin reprograms the TIME to an activated status and may be a suitable immune response modifier for further investigation in patients with ESCC.